1988
DOI: 10.3109/00365548809117218
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to Campylobacter pylori in an Ethnic Group Lacking Peptic Ulceration

Abstract: The association between duodenal ulcer, gastritis and gastroduodenal colonization with Campylobacter pylori suggests a causal role for this newly described bacterium. In an attempt to challenge the verity of this association we studied a group of people in whom duodenal ulcer is apparently absent. Serological evidence of infection was sought with a sensitive, specific ELISA assay for C. pylori specific IgG and was compared with results from control sera from teenagers referred for respiratory viral serology, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 12 publications
0
18
1
Order By: Relevance
“…Serologic studies suggested that the difference in the colonization rates of H. pylori was related to the ethnic backgrounds of the population studied. 24,25 In this study, the seropositive rate for preschool aboriginal children of Hsing-Yi and Jen-Ai townships in Nantou County was higher than that of any other ethnic groups. Similar observations were also reported in another study.…”
Section: Discussionmentioning
confidence: 49%
“…Serologic studies suggested that the difference in the colonization rates of H. pylori was related to the ethnic backgrounds of the population studied. 24,25 In this study, the seropositive rate for preschool aboriginal children of Hsing-Yi and Jen-Ai townships in Nantou County was higher than that of any other ethnic groups. Similar observations were also reported in another study.…”
Section: Discussionmentioning
confidence: 49%
“…The only other ethnic group that to our knowledge has a lower prevalence of H. pylori infection are the Australian aborigines (22,23). There is, however, a relatively higher prevalence of infection among the non-Malay minority in our area.…”
Section: Discussionmentioning
confidence: 54%
“…Nevertheless, detection of IgG antibodies has been proposed for several screening strategies [59,71]. Serology can be applied without restriction for epidemiological studies [74] and for follow-up after eradication therapy [60,75],…”
Section: Serological Detectionmentioning
confidence: 99%